Pemberdayaan Masyarakat Melalui Pengolahan Kulit Kakao - Nurul Inayah; Nur Anim Jauhariyah; Komarudin Komarudin; Mahbub Mahbub (IAI Darussalam, 2019)
Sumberagung Village is one of the villages in Banyuwangi Regency which is in the southern region precisely at the foot of Mount Tumpang Pitu, Mount Lompong, Mount Bayur, and Bukit Kapur (Gunung Gamping). The village has the potential of cocoa plants. There is a problem of wasted cocoa skin waste, so we took the initiative to help the community to reduce cocoa skin waste by utilizing food preparations that could add to the economy in Sungailembu Hamlet. So that the cocoa skin waste will have a high selling value, and can be used as a typical product of the Sungailembu Hamlet. Therefore, to help with the problem of reducing cocoa skin waste, a training was held in Sungailembu Hamlet, which was attended by IIK (Employees 'Wives' Association) housed in the Punta Dewa building. By giving direction on the innovation of cocoa skin waste to be processed into cocoa skin crackers.